The human transcript database: a catalogue of full length cDNA inserts. - Bouck, J; McLeod, M P; Worley, K; Richard A Gibbs (Bioinformatics, 2000)
SUMMARY: Full length cDNA sequences are an important resource for the research community but are currently intermingled with other sequences. We have identified the human full length insert cDNA sequences in GenBank and placed them in a single location, the Human Transcript Database. AVAILIBILITY: The Human Transcript Database is available at http://www.hgsc.bcm.tms.edu/HTDB/. CONTACT: John Bouck: jbouck@bcm.tmc.edu
Keywords: Databases, Factual; DNA Transposable Elements; DNA, Complementary; Humans; RNA, Messenger